Residents’ Perception Of Surgical Theatre Educational Environment At Public Hospitals Of Rawalpindi - A Steem Survey - Ijaz, Osama; Khan, Aurangzeb; Farooqui, Marryam Riaz; Bhatti, Hamza Waqar; Rauf, Fatima; Malik, Naveed Akhtar (Journal of Rawalpindi Medical College, 2023)
INTRODUCTION: The experience in the operation theatres is pivotal for surgical education. A measure of the educational environment in the operating room as perceived by residents would assist educators and trainees in gauging the quality of the learning occurring within their institute. METHODS: A cross-sectional survey using the surgical theatre educational environment measure (STEEM) 40-item inventory to measure theatre learning environment perception of surgery and allied residents in public sector hospitals of Rawalpindi. Internal reliability of the inventory was assessed using the Cronbach α coefficient. P≤ 0.05 was considered significant. RESULTS: 107 respondents were included in the study. Mean score of the survey was 133.7± 20.2. No significant differences in perception were found among residents at different stages and gender, except in learning subscale of the inventory for both gender and residents and the teaching and training subscale among residents at different levels. The inventory showed a high internal consistency with a Cronbach α of 0.851. CONCLUSION: Surgical training and education have still a long way to go in the public sector. Much needed collaborations with education specialist and senior surgeons is required. Interval collection of feedback and perceptions of the educational environment is also necessary.